Participation of inmigrant families and interculturaleducation in the school - Juan José Leiva Olivencia (Universidad de La Rioja, 2013)
This paper focuses its gaze on the participation of immigrant families in the school context, analyzing this participation as a key initiative in the generation and development of intercultural educational coexistence within the framework of educational institutions seeking to be inclusive. In this sense, we argue that multiculturalism requires active and democratic practices as the school community participation in educational settings of cultural diversity, and enabling more young people to learn models of relationships and positive social values. Indeed, a recent research study conducted in public schools Primary and Secondary Education in the province of Malaga, confirms the growing tendency to consider the importance of promoting intercultural and the involvement of immigrant families to improve the construction of a school life intercultural and inclusive.